1993
DOI: 10.1148/radiology.188.1.8511296
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology of nonpalpable breast lesions: US versus stereotaxic guidance.

Abstract: The authors evaluated ultrasound (US)-guided fine-needle aspiration cytology (FNAC) in 270 patients with suspicious findings at mammography. FNAC with a 10-MHz transducer and real-time scanner was performed when a lesion seen mammographically was unequivocally depicted at US. The needle was inserted with variable obliquity to the scanning plane. Stereotaxically guided FNAC was performed when lesions were not visible at US. High suspicion at mammography and positive cytologic reports led to surgical biopsy. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
4

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 0 publications
4
28
1
4
Order By: Relevance
“…In fact, in our follow-up mammograms no cancer has appeared among the 34 nodules with an insufficient/inadequate cytological result. This is probably related to the estimates made by Ciatto et al [16] in the sense that the opacities with smooth margins show a higher inadequacy rate in FNAB owing to the poor cellularity of these lesions, most of which are fibroadenomas [16,17]. On the other hand, our inadequacy rate is at the level of most authors [2,6,13,16], although others have also published series with very low rates [3,15,17].…”
Section: Discussionmentioning
confidence: 59%
“…In fact, in our follow-up mammograms no cancer has appeared among the 34 nodules with an insufficient/inadequate cytological result. This is probably related to the estimates made by Ciatto et al [16] in the sense that the opacities with smooth margins show a higher inadequacy rate in FNAB owing to the poor cellularity of these lesions, most of which are fibroadenomas [16,17]. On the other hand, our inadequacy rate is at the level of most authors [2,6,13,16], although others have also published series with very low rates [3,15,17].…”
Section: Discussionmentioning
confidence: 59%
“…Because of these controversies and the pos sible limitations of large-core breast biopsy, some groups continue to perform fine-needle aspiration biopsy [16,17]. Thus, even support ers of 14-gauge needles in breast core biopsy would welcome a prospective comparative study of different needle sizes [18].…”
Section: Conclusion Ourresults Indicate That Thequantity Andquality mentioning
confidence: 99%
“…In the present study, we showed that this technique is useful and sensitive for the diagnosis and management of small and nonpalpable breast masses. A few investigators have reported on the accuracy and clinical usefulness of this technique [16][17][18]. However, previous studies did not describe the management of breast masses and staging of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FNAB under US guidance was first reported in 1987 [15]. There are few reports, however, on the usefulness of FNAB under US guidance [16][17][18] and there has been no report of clinical management of nonpalpable or small mases based on FNAB under US guidance.…”
Section: Introductionmentioning
confidence: 99%